Structural modeling analysis of digital literacy and entrepreneur on sustainability performance through innovation capability in MSMEs - Nurhaerah, Nurhaerah; JR, Muh. Taftazani (Jurnal Mantik, 2025)
MSMEs in Indonesia, including in Mamuju City, face major challenges in improving their sustainability performance amidst global competition and rapid technological developments. The purpose of this study is to examine the significance of digital literacy and entrepreneur literacy in improving sustainability performance through innovation capability among Micro, Small, and Medium Enterprises (MSMEs). The research object is focused on MSME actors in the Manakarra Beach Pavilion area of Mamuju City, which is the largest MSME area in Mamuju City, West Sulawesi Province. This study employed a cross-sectional survey and a quantitative methodology method by developing a path analysis model. The population was all MSME actors in the area, and a purposive sampling method was employed to choose the sample. This study had 215 samples or respondents. This study used validity and reliability tests to ensure data accuracy. The study used statistical analytic methods and multiple linear regression using the SPSS version 20 software.  The results of the research that has been conducted found that digital literacy and entrepreneurial literacy play a significant role in improving the sustainability performance of MSMEs, both directly and indirectly through innovation capability as a mediating variable. According to the study's findings, digital literacy and, Entrepreneur Literacy, and Innovation Capability on Sustainability Performance among MSME actors in Mamuju City